Extracts from the history and medical properties of garlic - Petrovska, Biljana Bauer; Cekovska, Svetlana (Pharmacognosy Reviews, 2010)
At the time when antibiotics and other pharmacy products did not exist, a bulb of garlic itself represented a whole pharmacy industry due to the broad spectrum of effects. Most different suppositions involving this herb are mentioned; some of them were so pointless that they disappeared in time, but some of them have remained until the present days. The garlic was given different names that are still in use such as ‘Russian penicillin’, ‘natural antibiotic’, ‘vegetable viagra’, ‘plant talisman’, ‘rustic’s theriac’, ‘snake grass’ etc. Presentation of the development of ideas associated with garlic and the evolution of the notions increased the ability of the pharmacists and physicians to respond to the challenges of their professional services in facilitating human life.
Keywords: Allium sativum; garlic; history; usage